2005
DOI: 10.2139/ssrn.816704
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Legal Threats on Online Music Sharing Activity: An Analysis of Music Industry Legal Actions

Abstract: The music industry has repeatedly expressed concerns over potentially devastating impacts of online music sharing. Initial attempts to control online file sharing have been primarily through consumer education and legal action against the operators of networks that facilitated file sharing. Recent legal action against individual file sharers marked an unprecedented shift in the industry's strategy. The focus now is on wellpublicized legal threats and actions on a relatively small group of individuals to discou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…For example, Oberholzer-Gee and Strumpf claim that ''[w]hile the majority of papers reports some sales displacement, the four studies using actual measures of file-sharing find that file-sharing is unrelated to changes in sales'' and the Andersen and Frenz study is not even included in this group. The studies that Oberholzer-Gee and Strumpf reference in this quote (in addition to their own 2007 article) are as follows: Bhattacharjee et al (2006), Tanaka (2004) and Smith and Telang (2008). The reader may ask why I am not including these three studies in the list of studies not finding harm from file-sharing.…”
Section: Applying the Metric To The Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…For example, Oberholzer-Gee and Strumpf claim that ''[w]hile the majority of papers reports some sales displacement, the four studies using actual measures of file-sharing find that file-sharing is unrelated to changes in sales'' and the Andersen and Frenz study is not even included in this group. The studies that Oberholzer-Gee and Strumpf reference in this quote (in addition to their own 2007 article) are as follows: Bhattacharjee et al (2006), Tanaka (2004) and Smith and Telang (2008). The reader may ask why I am not including these three studies in the list of studies not finding harm from file-sharing.…”
Section: Applying the Metric To The Literaturementioning
confidence: 98%
“…First, I did not include Bhattacharjee et al (2006) because that article does not conclude that the impact of file-sharing on sales is benign. Here is how Dr. Bhattacharjee characterized his article's results:…”
Section: Applying the Metric To The Literaturementioning
confidence: 99%
“…Bhattacharjee et al (2006) tracked the file-sharing activities of 2056 people before and after RIAA-related lawsuits and found that respondents' sharing behavior decreased significantly around the time of RIAA legislative activity but then, after a period of time, returned to its original level. To the best of our knowledge, no such longitudinal studies with educational strategies have been conducted, but, based on our results, perhaps a different approach would be more suitable-one focused not on preventing piracy from occurring but on offering better service value than that promised by pirating files (Jeong and Khouja 2013).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…In 2001, the RIAA began pursuing lawsuits against firms that facilitate music piracy, and in 2003, the RIAA began pursuing lawsuits against suspected large-scale individual file-sharers, and continues to this day. While studies have shown some reduction in file-sharing, the extent of file-sharing remains substantial (Bhattacharjee et al 2006). Yet, despite these actions, the RIAA acknowledges the value of the Internet as a medium for disseminating music and strongly supports fee-based online music services that provide a legal alternative to file-sharing.…”
Section: The Role Of Technology In Musicmentioning
confidence: 99%